Cultural Variations in Public Beliefs about Mental Disorders: A Comparison between Tunisia and Germany - Angermeyer, Matthias C. (Clin Pract Epidemiol Ment Health, 2020)
BACKGROUND: In recent years there is a growing interest in public beliefs about mental disorders. Numerous representative population-based studies have been conducted around the globe, also in European countries bordering on the Mediterranean Sea. However, relatively little is known about public beliefs in countries in Northern Africa. OBJECTIVE: To fill this gap by comparing public beliefs about mental disorders in Tunisia and Germany, focusing on causal beliefs, help-seeking recommendations and treatment preferences. METHODS: Representative national population-based surveys have been conducted in Tunisia in 2012 (N = 811) and in Germany in 2011 (N = 1852), using the same interview mode and the same fully structured interview starting with a vignette depicting a person suffering from either schizophrenia or depression. RESULTS: In Tunisia, the public was more likely to adopt psychosocial and to reject biogenetic explanations than in Germany. Correspondingly, psychological treatments were more frequently recommended and biological ones more frequently advised against. There was also a strong inclination to share religious beliefs and to recommend seeking religious advice. Tunisians tended much more than Germans to hold moralistic views and to blame the afflicted person for his or her illness. In Tunisia, the public tended less to differentiate between schizophrenia and depression than in Germany. CONCLUSION: Marked differences between Tunisia and Germany exist in public beliefs about the causes of mental disorders and their treatment, which correspond to differences in cultural orientations prevailing in these countries. Mental health professionals need to be sensitive to the particular cultural context in which they operate, in order to be able to reach those they intend to care for.